Earnings Inequality Within and Across Gender, Racial, and Ethnic Groups in Four Latin American Countries - Cunningham, Wendy (World Bank, Washington, DC, 2012)
Latin American countries are generally characterized as displaying high income and earnings inequality overall along with high inequality by gender, race, and ethnicity. However, the latter phenomenon is not a major contributor to the former phenomenon. Using household survey data from four Latin American countries (Bolivia, Brazil, Guatemala, and Guyana) for which stratification by race or ethnicity is possible, this paper demonstrates (using Theil index decompositions as well as Gini indices, and 90/10 and 50/10 percentile comparisons) that within-group earnings inequality rather than between-group earnings inequality is the main contributor to overall earnings inequality. Simulations in which the relatively disadvantaged gender and/or racial/ethnic group is treated as if it were the relatively advantaged group tend to reduce overall earnings inequality measures only slightly and in some cases have the effect of increasing earnings inequality measures.